Polyvinyl acetal resin, conductive paste, and multilayer ceramic capacitors
Patent Information
- Application Number
- JP2026058588
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-31
- Filing Date
- 2026-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0058】 本発明によれば、溶剤溶解性が良く、強度が高く、密着性に優れる導電層を得ることが可能なポリビニルアセタール樹脂、及び、該ポリビニルアセタール樹脂を用いた導電ペースト及び積層セラミックコンデンサを提供できる。 また、本発明によれば、溶剤溶解性が高く、適度な粘度を有する導電ペーストを得ることができる。
Smart Images

Figure 2026167653000001 
Figure 2026167653000002 
Figure 2026167653000003
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to a polyvinyl acetal resin, a conductive paste, and a multilayer ceramic capacitor.
BACKGROUND ART
[0002] Multilayer electronic components such as multilayer circuit boards, multilayer coils, and multilayer ceramic capacitors are widely used. Among these, multilayer ceramic capacitors are generally manufactured through the following processes. First, ceramic raw material powder is added to a solution obtained by dissolving a binder resin such as a polyvinyl butyral resin or a poly(meth)acrylate resin in an organic solvent, and the mixture is uniformly mixed to obtain a ceramic slurry composition. This slurry composition is cast onto a support, volatile components such as the solvent are removed by heating or the like, and the resulting product is peeled off from the support to obtain a ceramic green sheet. Next, a plurality of the obtained ceramic green sheets each coated with a conductive paste for internal electrodes by screen printing or gravure printing are alternately stacked and thermocompression bonded to produce a laminate. Thereafter, a treatment for thermally decomposing and removing the binder resin component and the like contained in the laminate, a so-called degreasing treatment, is performed, followed by a step of sintering external electrodes on the end faces of a ceramic sintered body obtained by firing, whereby a multilayer ceramic capacitor is obtained.
[0003] The conductive paste for internal electrodes is obtained by kneading conductive powder, an organic solvent, and a binder resin. As the binder resin, ethyl cellulose and polyvinyl acetal resin are used. However, when a polyvinyl acetal resin is used as the binder resin, there is a problem that stringing occurs when the paste is printed by screen printing. Patent Document 1 discloses a conductive paste containing a carboxylic acid-modified polyvinyl acetal resin, an organic solvent, and conductive powder from the viewpoint of ameliorating the above problem. In addition, Patent Document 2 discloses a conductive paste containing a polyvinyl acetal resin having an ethylene group from the viewpoint of ameliorating the above problem. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2017-228780 [Patent Document 2] Japanese Patent Publication No. 2008-285590 [Overview of the project] [Problems that the invention aims to solve]
[0005] In recent years, with the miniaturization and increased capacitance of multilayer ceramic capacitors, both the ceramic layer (dielectric layer) and the internal electrode layer (conductive layer) have been further multilayered and thinned. However, as the thickness decreases, conventional polyvinyl acetal resins cannot provide internal electrode layers with sufficient strength, leading to problems such as tearing and breakage during lamination due to insufficient strength, and a decrease in yield. There is also the problem of reduced adhesion between the dielectric layer and the internal electrode layer.
[0006] The present invention aims to provide a polyvinyl acetal resin capable of producing a conductive layer with good solvent solubility, high strength, and excellent adhesion, as well as a conductive paste and a multilayer ceramic capacitor using the polyvinyl acetal resin. [Means for solving the problem]
[0007] Disclosure 1 is a polyvinyl acetal resin in which the ratio of the relaxation time T1ρ[T] obtained from the side-chain terminal carbon to the average relaxation time T1ρ[MC] of the acetal carbon and methine carbon, calculated by solid-state NMR, is 1.3 or greater (T1ρ[T] / T1ρ[MC]). Disclosure 2 has a constituent unit represented by the following formula (1), wherein R in the following formula (1) 1 The polyvinyl acetal resin according to Disclosure 1 is a linear hydrocarbon group having 4 to 20 carbon atoms and having an average degree of polymerization of less than 2300. [ka] Disclosure 3 is a polyvinyl acetal resin according to Disclosure 1 or 2, wherein the glass transition temperature is 60°C or lower. Disclosure 4 is a polyvinyl acetal resin according to any one of Disclosures 1 to 3, wherein the hydroxyl group content is 10 mol% or more and 25 mol% or less. Disclosure 5 is a polyvinyl acetal resin according to any one of Disclosures 1 to 4, wherein the content of the constituent unit represented by formula (1) is 5 mol% or more and 45 mol% or less. Disclosure 6 is a conductive paste containing a polyvinyl acetal resin as described in any of Disclosures 1 to 5, an organic solvent, a conductive powder, and a dispersion improver. Disclosure 7 is a multilayer ceramic capacitor made using the conductive paste described in Disclosure 6.
[0008] As a result of diligent research, the inventors of the present invention have discovered that polyvinyl acetal resins with a relaxation time (T1ρ[T] / T1ρ[MC]) calculated by solid-state NMR within a predetermined range can be used to obtain conductive layers with good solvent solubility, high strength, and excellent adhesion, thus completing the present invention.
[0009] In one embodiment of the present invention, the polyvinyl acetal resin has a ratio (T1ρ[T] / T1ρ[MC], also referred to as the relaxation time ratio) of 1.3 or higher to the average relaxation time T1ρ[MC] between the acetal carbon and methine carbon, calculated by solid-state NMR, which is obtained from the relaxation time T1ρ[T] obtained from the side-chain terminal carbon. By having the above relaxation time ratio within the above range, the strength (especially the fracture strain) is high and the strength of the conductive layer can be improved. In this invention, the average relaxation time T1ρ[MC] is the average relaxation time of the acetal carbon and methine carbon in the polyvinyl acetal resin, and therefore reflects the characteristics of a region relatively close to the main chain, while the relaxation time T1ρ[T] obtained from the carbons at the ends of the side chains reflects the characteristics of a region farther away from the main chain. Therefore, T1ρ[T] / T1ρ[MC] serves as an indicator of the degree of aggregation between the ends of the side chains. The above average relaxation time T1ρ[MC] can be derived by measuring the relaxation time of acetal carbon and the relaxation time of methine carbon in polyvinyl acetal resin, and then calculating the average value (for example, [relaxation time of acetal carbon + relaxation time with methine carbon] / 2). Furthermore, the acetal carbon refers to the carbon atom bonded to two oxygen atoms and the hydrocarbon portion of the acetal unit, the methine carbon refers to the carbon atom bonded to one oxygen atom of the acetal unit and constituting the main chain, and the side-chain terminal carbon refers to the carbon atom located at the end of the hydrocarbon portion of the acetal unit. In addition, if the hydrocarbon portion of the acetal unit is a branched chain, the carbon atom at the end of the longest chain is considered the side-chain terminal carbon. Furthermore, if the hydrocarbon portion of the acetal unit consists of multiple types, the carbon atom at the end of the hydrocarbon portion with the most carbon atoms is considered the side-chain terminal carbon. The preferred lower limit of the relaxation time ratio is 2.0, and the more preferred lower limit is 3.5. The preferred upper limit of the relaxation time ratio is 8.2, and the more preferred upper limit is 6.7. Setting the ratio above the lower limit results in higher fracture strain and improved sheet strength, while setting it below the upper limit improves solubility in solvents, enhances the strength of the conductive layer, and improves adhesion to the ceramic green sheet (dielectric layer).
[0010] Solid-state NMR measurement of polyvinyl acetal resin according to one embodiment of the present invention is performed by the following method. A polyvinyl acetal resin according to one embodiment of the present invention is packed into the center of a solid-state NMR sample tube and subjected to a solid-state NMR measuring device (e.g., JEOL Ltd., ECZ-400R), and the observed nuclei are measured at room temperature. 13 C. The observation frequency was set to 10 kHz and the pulse width to 2.93 μs, and the relaxation times of acetal carbon, methine carbon, and side-chain terminal carbon in polyvinyl acetal resin were measured. In one embodiment of the present invention, in solid-state NMR measurement of polyvinyl acetal resin, 13After determining the relaxation times of carbon nuclei corresponding to acetal carbons, which are attributed to peaks around 88 ppm to 105 ppm in the 1C-NMR spectrum, and the relaxation times of carbon nuclei corresponding to methine carbons, which are attributed to peaks around 57 ppm to 90 ppm, the average value of these relaxation times, T1ρ[MC], is calculated. Furthermore, the relaxation time T1ρ[T] of the carbon nucleus corresponding to the side-chain terminal methine carbon, which is attributed to the peak around 10 ppm to 30 ppm, is determined. Then, the ratio (T1ρ[T] / T1ρ[MC]) of the relaxation time T1ρ[T] obtained from the side-chain terminal carbon to the average relaxation time T1ρ[MC] of the acetal carbon and methine carbon is calculated.
[0011] The relaxation time ratio described above can be adjusted by the acetalization conditions, such as the aldehyde input temperature and catalyst temperature, the amount of hydroxyl groups, acetal groups, and acetyl groups in the polyvinyl acetal resin, the structure of the acetal unit (number of carbon atoms in the alkyl group), and the type of modifying group. In particular, it is preferable to adjust it by the structure of the acetal unit (number of carbon atoms in the alkyl group). Specifically, the number of carbon atoms in the alkyl group of the acetal unit is preferably 4 to 20, and more preferably 6 or 9.
[0012] A polyvinyl acetal resin according to one aspect of the present invention has a constituent unit represented by the following formula (1), wherein R in the following formula (1) 1 However, it is preferable that the hydrocarbon group is linear, has 4 to 20 carbon atoms, and has an average degree of polymerization of less than 2300. This makes it possible to obtain a conductive layer with high strength and excellent adhesion.
[0013] [ka]
[0014] The above R 1 The number of carbon atoms is 4 or more and 20 or less, preferably 5 or more. A more preferable lower limit for the number of carbon atoms is 6, a preferred upper limit is 15, and a more preferable upper limit is 10. In particular, the above R 1 The number of carbon atoms is preferably 6 or 9. 1This may be a combination of two or more hydrocarbon groups with different numbers of carbon atoms.
[0015] As the hydrocarbon group having 4 to 20 carbon atoms, alkyl groups having 5 to 20 carbon atoms are preferred, and alkyl groups having 5 to 10 carbon atoms are more preferred. Examples of alkyl groups having 4 to 20 carbon atoms include butyl group, pentyl group, hexyl group, heptyl group, octyl group, nonyl group, decyl group, undecyl group, dodecyl group, tridecyl group, tetradecyl group, pentadecyl group, hexadecyl group, heptadecyl group, octadecyl group, nonadecyl group, eicosyl group, and the like.
[0016] The hydrocarbon group having 4 to 20 carbon atoms may be a linear alkyl group or a branched alkyl group, but it is preferable that it be linear. Examples of the linear alkyl groups mentioned above include n-butyl group, n-pentyl group, n-hexyl group, n-heptyl group, n-octyl group, n-nonyl group, n-decyl group, n-undecyl group, n-dodecyl group, n-tridecyl group, n-tetradecyl group, n-hexadecyl group, n-heptadecyl group, n-octadecyl group, n-nonadecyl group, and n-eicosyl group.
[0017] Examples of the branched alkyl groups mentioned above include isobutyl group, isopentyl group, neopentyl group, 1-methylhexyl group, 1-methylheptyl group, 1-methyloctyl group, 1-methylnonyl group, 1-methyldecyl group, 1-methylundecyl group, and 1-methyldodecyl group. Other examples include 1-methyltridecyl group, 1-methyltetradecyl group, 1-methylheptadecyl group, 1-methylhexadecyl group, 1-methylpentadecyl group, 1-methyloctadecyl group, and 1-methylnonadecyl group. Furthermore, examples include alkyl groups in which an alkyl group having two or more carbon atoms is substituted on the carbon atom at position 1 (for example, 1-ethyldecyl group, 1-propylnonyl group, 1-butyloctyl group, 1-pentylheptyl group, 1-octyldecyl group, etc.). Further, in a branched alkyl group, the branching position is not limited to the carbon atom at the 1-position, and may be a carbon atom at the 2-position or higher. For example, examples of the alkyl group in which a methyl group is substituted on a carbon atom at the 2-position or higher include 2-methylundecyl, 3-methylundecyl, and 4-methylundecyl groups. Examples of the alkyl group in which an alkyl group having 2 or more carbon atoms is substituted on a carbon atom at the 2-position or higher include 2-ethylhexyl group, 2-ethylheptyl group, 2-ethyloctyl group, 2-ethylundecyl group, 2-ethyloctadecyl group, 2-propylundecyl group, 2-butylundecyl group, and 2-octylundecyl group. Further examples include 3-ethylundecyl group, 4-ethyloctadecyl group, 4-butyloctadecyl group, neodecyl group, and the like.
[0018] In the present invention, the hydrocarbon group having 4 to 20 carbon atoms is preferably a linear alkyl group. Further, the alkyl group having 4 to 20 carbon atoms may be composed of two or more types of alkyl groups including a linear alkyl group and a branched alkyl group, or may be composed only of a linear alkyl group. In addition, R in the following formula (1) 1 may be an alkyl group derived from a bio-based aldehyde having 4 to 20 carbon atoms.
[0019] With respect to the content of the structural unit represented by the above formula (1) in the polyvinyl acetal resin according to one aspect of the present invention, a preferred lower limit is 5 mol%, a more preferred lower limit is 10 mol%, a still more preferred lower limit is 20 mol%, a preferred upper limit is 85 mol%, a more preferred upper limit is 45 mol%, and a still more preferred upper limit is 42 mol%. As a result, excellent solubility in a solvent, high paste viscosity, good thixotropy, and favorable printability can be achieved. The content of the structural unit represented by the above formula (1) is 1 H-NMR and 13 C-NMR (nuclear magnetic resonance spectrum).
[0020] A polyvinyl acetal resin according to one aspect of the present invention preferably further has acetal units represented by the following formula (2), which are different from the constituent units represented by the above formula (1). Having acetal units represented by the following formula (2) makes it possible to improve solubility in solvents.
[0021] [ka] In formula (2), R 2 This represents an alkyl group having 1 to 3 carbon atoms. The above R 2 The alkyl group preferably has 1 or more carbon atoms. The preferred upper limit for the carbon number is 2.
[0022] The above R 2 Examples of alkyl groups having 1 to 3 carbon atoms include methyl, ethyl, and propyl groups. 2 The alkyl group having 1 to 3 carbon atoms may be linear or branched.
[0023] In a polyvinyl acetal resin according to one embodiment of the present invention, the content of acetal units represented by formula (2) is preferably 10 mol%, more preferably 15 mol%, even more preferably 30 mol%, preferably 80 mol%, more preferably 75 mol%, and even more preferably 66 mol%. By keeping the content of acetal units represented by formula (2) within the above range, good solubility in solvents can be achieved. The content of acetal units represented by formula (2) is 1 H-NMR and 13 Measurements are performed using 1C-NMR (nuclear magnetic resonance spectroscopy).
[0024] In one embodiment of the present invention, when the polyvinyl acetal resin contains acetal units represented by formula (1) and acetal units represented by formula (2), the total content of these units is preferably 63 mol%, more preferably 65 mol%, even more preferably 70 mol%, particularly preferably 75 mol%, preferably preferably 95 mol%, more preferably 90 mol%, even more preferably 89 mol%, and particularly preferably 88 mol%. By keeping the total content within the above range, it is possible to prevent separation of conductive powder during storage, maintain good viscosity stability over time, and achieve good solubility in solvents.
[0025] In one embodiment of the present invention, when the polyvinyl acetal resin contains acetal units represented by formula (1) and acetal units represented by formula (2), the ratio of the two (content of acetal units represented by formula (1) / content of acetal units represented by formula (2)) is preferably 0.19 or more and 5.4 or less, and more preferably 0.3 or more and 1.5 or less. By keeping the ratio within the above range, it is possible to prevent the separation of conductive powder during storage, maintain good viscosity stability over time, and achieve good solubility in solvents.
[0026] In one embodiment of the present invention, the total amount of acetal groups (sum of all acetal units) in the polyvinyl acetal resin is preferably 71 mol% or more. By keeping the total amount of acetal groups within the above range, a conductive layer with high strength and excellent adhesion can be obtained. The preferred lower limit for the total amount of acetal groups is 62 mol%, a more preferred lower limit is 65 mol%, an even more preferred lower limit is 70 mol%, a particularly preferred lower limit is 75 mol%, a preferred upper limit is 95 mol%, a more preferred upper limit is 90 mol%, an even more preferred upper limit is 89 mol%, and a particularly preferred upper limit is 88 mol%. The total amount of acetal groups is 1 H-NMR and 13 Measurements are performed using 1C-NMR (nuclear magnetic resonance spectroscopy). Furthermore, the content of the constituent unit represented by formula (1) relative to the total amount of acetal groups (content of the constituent unit represented by formula (1) / total amount of acetal groups) has a preferred lower limit of 0.07, a more preferred lower limit of 0.20, a preferred upper limit of 0.9, and a more preferred upper limit of 0.6.
[0027] A polyvinyl acetal resin according to one aspect of the present invention has constituent units having hydroxyl groups. In one embodiment of the present invention, the content of the hydroxyl group-containing structural units (hydroxyl group amount) in the polyvinyl acetal resin is preferably 10 mol% or more and 25 mol% or less. By keeping it within this range, a conductive layer with high strength and excellent adhesion can be obtained. The more preferable lower limit for the amount of hydroxyl groups is 12 mol%, and the more preferable upper limit is 23 mol%. 1 H-NMR and 13 Measurements are performed using 1C-NMR (nuclear magnetic resonance spectroscopy).
[0028] A polyvinyl acetal resin according to one aspect of the present invention has constituent units having acetyl groups. In one embodiment of the present invention, the preferred lower limit of the content of the constituent units having the acetyl group (amount of acetyl groups) in the polyvinyl acetal resin is 0.1 mol%, and the preferred upper limit is 10 mol%. By setting the amount of acetyl groups to 0.1 mol% or more, good solubility in the solvent can be achieved, and by setting the amount of acetyl groups to 10 mol% or less, good solubility in the solvent can be achieved. A more preferred lower limit of the amount of acetyl groups is 0.3 mol%, and a more preferred upper limit is 5 mol%. The above acetyl group 1 H-NMR and 13 Measurements are performed using 1C-NMR (nuclear magnetic resonance spectroscopy).
[0029] The polyvinyl acetal resin according to one aspect of the present invention may have constituent units having a carboxylic acid. In one embodiment of the present invention, the preferred lower limit of the content of the carboxylic acid-containing structural unit (carboxylic acid modification amount) in the polyvinyl acetal resin is 0.1 mol%, and the preferred upper limit is 10 mol%. By setting the amount of carboxylic acid groups to 0.1 mol% or more, the paste viscosity can be increased, and by setting the amount of carboxylic acid modification to 10 mol% or less, solubility in solvents can be improved. A more preferred lower limit of the amount of acetyl groups is 0.3 mol%, and a more preferred upper limit is 5 mol%. The above amount of carboxylic acid modification 1 H-NMR and 13 Measurements are performed using 1C-NMR (nuclear magnetic resonance spectroscopy). The carboxylic acid of the constituent unit having the above-mentioned carboxylic acid is not particularly limited, and examples include itaconic acid, crotonic acid, maleic acid, phthalic acid, etc.
[0030] In one embodiment of the present invention, the polyvinyl acetal resin preferably has an average degree of polymerization of less than 2300. This improves the initial dispersibility of the conductive powder, thereby improving the viscosity stability of the conductive paste. In one embodiment of the present invention, the polyvinyl acetal resin has an average degree of polymerization of preferably 200 or more, and preferably less than 2300. An average degree of polymerization of 200 or more enhances the initial dispersibility of the conductive powder, thereby improving the viscosity stability of the conductive paste. An average degree of polymerization of less than 2300 enhances the dispersion retention capacity of the conductive powder, thereby improving the viscosity stability of the conductive paste. More preferably, the average degree of polymerization is 700 or more, and more preferably less than 1800. The average degree of polymerization of the polyvinyl acetal resin can be determined from the polyvinyl alcohol used as the raw material.
[0031] A polyvinyl acetal resin according to one aspect of the present invention may be copolymerized with ethylenically unsaturated monomers, to the extent that the effects of the present invention are not impaired. The above ethylenically unsaturated monomers are not particularly limited and include, for example, acrylic acid, methacrylic acid, (anhydride) phthalic acid, (anhydride) maleic acid, (anhydride) itaconic acid, etc. Also, acrylonitrile, methacrylonitrile, acrylamide, methacrylamide, trimethyl-(3-acrylamido-3-dimethylpropyl)-ammonium chloride, acrylamide-2-methylpropanesulfonic acid and its sodium salt, etc. Furthermore, ethyl vinyl ether, butyl vinyl ether, N-vinylpyrrolidone, vinyl chloride, vinyl bromide, vinyl fluoride, vinylidene chloride, vinylidene fluoride, tetrafluoroethylene, sodium vinylsulfonate, sodium allylsulfonate, etc. In addition, terminally modified polyvinyl alcohols obtained by copolymerizing vinyl ester monomers such as vinyl acetate with ethylene in the presence of thiol compounds such as thiol acetate and mercaptopropionic acid, and then saponifying the mixture, can also be used.
[0032] In one embodiment of the present invention, the polyvinyl acetal resin preferably has a glass transition temperature (Tg) of 60°C or lower. This ensures adhesion between the composition (conductive paste) containing the polyvinyl acetal resin and the ceramic green sheet. The preferred lower limit of the glass transition temperature is 25°C, a more preferred lower limit is 30°C, a preferred upper limit is 58°C, and a more preferred upper limit is 55°C. The above glass transition temperature can be measured, for example, using a differential scanning calorimeter (DSC).
[0033] The above glass transition temperature can be adjusted by the degree of polymerization of the polyvinyl acetal resin, the amount of hydroxyl groups, the amount of acetal groups, the amount of acetyl groups, the structure of the acetal units (number of carbon atoms in the alkyl group), the type and content of the modifying group, etc.
[0034] Methods for producing the above-mentioned polyvinyl acetal resin include methods for acetalizing polyvinyl alcohol using an aldehyde, and methods for acetalizing a polyvinyl acetal resin having acetal units represented by formula (1) using an aldehyde having 5 to 21 carbon atoms. In particular, it is preferable to use a method for acetalizing polyvinyl alcohol using at least one aldehyde having 5 to 21 carbon atoms. By using such a production method, the glass transition temperature can be adjusted.
[0035] In the method of acetalizing the above-mentioned polyvinyl alcohol using at least one aldehyde having 5 to 21 carbon atoms, examples include preparing aldehydes with different carbon number configurations and then introducing acetal units having multiple alkyl groups with different carbon number configurations by acetalization. When producing the above-mentioned polyvinyl acetal resin, acetalization may be carried out in the presence of a dispersant. More specifically, one method is to introduce the acetal unit represented by formula (1) by acetalizing polyvinyl alcohol that does not have the acetal unit represented by formula (1) with a predetermined aldehyde.
[0036] The above polyvinyl alcohol can be obtained, for example, by saponifying a vinyl ester polymer. Examples of vinyl esters include vinyl formate, vinyl acetate, vinyl propionate, and vinyl pivalate. Among these, vinyl acetate is preferred from an economic standpoint.
[0037] The polyvinyl alcohol resin described above preferably has a degree of saponification of 85 mol% or more. The degree of saponification is more preferably 90 mol% to 99.9 mol%, and even more preferably 95 mol% to 99.4 mol%. That is, the degree of saponification is preferably 90 to 99.9 mol%, and more preferably 95 to 99.4 mol%.
[0038] In the method of reacting the polyvinyl alcohol described above with an aldehyde having 5 to 21 carbon atoms, the aldehyde used in the acetalization reaction is not particularly limited, and examples include linear aliphatic aldehydes and branched aliphatic aldehydes having 5 to 21 carbon atoms. Examples of aliphatic aldehydes having 5 to 21 carbon atoms include baleraldehyde, hexylaldehyde, 2-ethylbutyraldehyde, 2-ethylhexylaldehyde, heptylaldehyde, octylaldehyde, nonylaldehyde, decylaldehyde, undecylaldehyde, dodecylaldehyde, tridecylaldehyde, tetradecylaldehyde, pentadecylaldehyde, hexadecylaldehyde, heptadecylaldehyde, octadecylaldehyde, eicosylaldehyde, heneicosylaldehyde, trimethylhexylaldehyde, methyloctylacetaldehyde, and methylnonylacetaldehyde. These aldehydes may be used individually or in combination of two or more. Particularly preferred is the combination of an aldehyde having 5 to 21 carbon atoms and an aldehyde having 4 or fewer carbon atoms. Among these, acetaldehyde, butyraldehyde, decylaldehyde, and heptaldehyde are preferred aldehydes.
[0039] The amount of aldehyde added can be appropriately set according to the amount of acetal groups in the target polyvinyl acetal resin. In particular, it is preferable to add 50 mol% to 120 mol%, more preferably 55 mol% to 110 mol%, of 100 mol% of polyvinyl alcohol, as this allows the acetalization reaction to proceed efficiently and makes it easier to remove unreacted aldehydes. That is, the amount of aldehyde added is preferably 50 to 120 mol%, and more preferably 55 to 110 mol%.
[0040] In the acetalization step described above, in addition to the aldehyde having 5 to 21 carbon atoms, an aldehyde having a cyclic aliphatic group or an aromatic group may also be used. Examples of aldehydes having an aromatic group include benzaldehyde, cinnamaldehyde, 2-methylbenzaldehyde, 3-methylbenzaldehyde, 4-methylbenzaldehyde, p-hydroxybenzaldehyde, m-hydroxybenzaldehyde, phenylacetaldehyde, and β-phenylpropionaldehyde.
[0041] In the acetalization process described above, if an aldehyde with 5 or more carbon atoms is included, a dispersant may or may not be used, but it is preferable to use a dispersant. By using a dispersant in the acetalization process described above, the solvent solubility of the polyvinyl acetal resin can be improved. Furthermore, in the acetalization step described above, it is preferable to use a method in which the polyvinyl acetal resin precipitates during the acetalization reaction (precipitation method) compared with a method in which the reaction is carried out with the polyvinyl acetal resin dissolved (dissolution method). Moreover, when acetalization is carried out using the above-mentioned dispersant, it is preferable to use the above-mentioned precipitation method. When using the above-mentioned dispersant, the amount of dispersant added is preferably 1.5 parts by weight or more and 10 parts by weight or less, and more preferably 3 parts by weight or more and 8 parts by weight or less, per 100 parts by weight of polyvinyl alcohol resin.
[0042] Examples of the above-mentioned dispersants include sodium dodecyl sulfate, sodium dodecylbenzenesulfonate, polyvinylpyrrolidone, polyethylene glycol, polyvinyl alcohol, colloidal silica, polyoxyethylene polyoxypropylene cetyl ether, and polyoxyethylene polyoxypropylene lauryl ether. These dispersants may be used individually or in combination of two or more types. Among these, sodium dodecylbenzenesulfonate and polyoxyethylene polyoxypropylene cetyl ether are preferred.
[0043] Examples of the acid catalysts mentioned above include mineral acids, carboxylic acids, and sulfonic acids. Examples of the above-mentioned mineral acids include sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid. Examples of the carboxylic acids mentioned above include formic acid, acetic acid, and propionic acid. Examples of the above-mentioned sulfonic acids include p-toluenesulfonic acid, methanesulfonic acid, ethanesulfonic acid, and benzenesulfonic acid. These acid catalysts may be used individually or in combination of two or more. Among them, p-toluenesulfonic acid and hydrochloric acid are preferred.
[0044] The temperature at which the above-mentioned aldehyde is added (aldehyde addition temperature) is preferably 5°C or higher, more preferably 10°C or higher, even more preferably 12°C or higher, particularly preferably 32°C or higher, preferably 70°C or lower, more preferably 68°C or lower, and even more preferably 60°C or lower. Furthermore, the temperature at which the catalyst is added is preferably 5°C to 60°C, preferably 10°C to 50°C, and more preferably 12°C to 20°C. By setting the catalyst addition temperature within the above temperature range, the solvent solubility of the polyvinyl acetal resin can be improved. The retention time in the above acetalization reaction is preferably 0.5 hours or more and 5 hours or less, and more preferably 1 hour or more and 3 hours or less. Furthermore, the holding temperature in the above acetalization reaction is preferably 0°C or higher and 65°C or lower, and more preferably 5°C or higher and 60°C or lower. In addition, in the above acetalization reaction, it is preferable to perform the holding reaction at a low temperature, then raise the temperature and perform the holding reaction at a high temperature. When performing the holding reaction at a high temperature, the holding temperature is preferably 35°C or higher and 49°C or lower, and more preferably 40°C or higher and 47°C or lower. By keeping the holding time in the above acetalization reaction within the above temperature range, the solvent solubility of the polyvinyl acetal resin can be improved.
[0045] Applications of the polyvinyl acetal resin according to one embodiment of the present invention include, for example, binders and dispersants for conductive pastes, battery electrodes, secondary battery electrodes, etc., modifiers for adhesives based on epoxy resins, phenolic resins, etc., and binders for ceramic green sheets. In particular, when the polyvinyl acetal resin according to one embodiment of the present invention is used as a conductive paste, the paste viscosity after mixing with the conductive powder is high, and the thixotropy is good, making it possible to obtain a paste with excellent printability.
[0046] A conductive paste containing a polyvinyl acetal resin according to one aspect of the present invention, an organic solvent, a conductive powder, and a dispersion improver is also one aspect of the present invention.
[0047] The above organic solvent can be any organic solvent commonly used in conductive pastes. Examples of the above organic solvents include terpineol derivatives such as dihydroterpineol, terpinyl acetate, isovonyl acetate, dihydroterpinyl acetate, dihydroterpinyl methyl ether, and terpinyl methyl ether, hydrocarbon solvents such as mineral spirits, and ethers and esters such as dipropylene glycol monomethyl ether and dipropylene glycol monomethyl ether acetate. Among these, dihydroterpineol and dihydroterpinyl acetate are preferred. These organic solvents may be used individually or in combination of two or more.
[0048] The amount of the above organic solvent is not particularly limited, but a preferred lower limit is 100 parts by weight and a preferred upper limit is 10,000 parts by weight relative to 100 parts by weight of the polyvinyl acetal resin. When the amount of the above organic solvent is 100 parts by weight or more, the viscosity of the conductive paste can be set within a suitable range and the printability can be improved. When the amount of the above organic solvent is 10,000 parts by weight or less, the performance of the above polyvinyl acetal resin can be fully exhibited in the conductive paste. A more preferred lower limit for the amount of the above organic solvent relative to 100 parts by weight of the polyvinyl acetal resin is 200 parts by weight and a more preferred upper limit is 5,000 parts by weight.
[0049] The conductive powders mentioned above are not particularly limited and include, for example, powders made of nickel, aluminum, silver, copper, and alloys thereof. These conductive powders may be used individually or in combination of two or more. Among these, nickel is preferred because of its excellent conductivity.
[0050] The average particle size of the conductive powder is preferably 50 to 300 nm, and its shape is preferably approximately spherical. An average particle size of 50 nm or more allows for a suitable specific surface area of the conductive powder, thereby improving its dispersibility. An average particle size of 300 nm or less improves the surface smoothness after printing. Note that "approximately spherical" includes not only perfectly spherical particles but also particles with a shape close to spherical.
[0051] The amount of conductive powder used is not particularly limited, but a preferred lower limit is 100 parts by weight and a preferred upper limit is 10,000 parts by weight relative to 100 parts by weight of the polyvinyl acetal resin. If the amount of conductive powder blended is 100 parts by weight or more, the density of the conductive powder in the conductive paste can be kept within a sufficient range, resulting in excellent conductivity. If the amount of conductive powder blended is 10,000 parts by weight or less, the dispersibility of the conductive powder in the conductive paste can be improved, resulting in excellent printability. The amount of conductive powder blended is preferably 200 parts by weight and 5000 parts by weight relative to 100 parts by weight of the polyvinyl acetal resin.
[0052] Preferably, the conductive paste described above further contains ceramic powder in addition to the conductive powder. Including ceramic powder makes it easier to match the shrinkage behavior of the conductive powder during firing with that of the ceramic green sheet. The ceramic powder is not particularly limited, but barium titanate used in green sheets is preferred. The average particle size of the ceramic powder is not particularly limited, but it is preferably smaller than the average particle size of the conductive powder, and specifically, it is preferably 30 nm to 200 nm.
[0053] The conductive paste described above may appropriately contain plasticizers, lubricants, antistatic agents, dispersion enhancers, surfactants, etc., to the extent that it does not impair the effects of the present invention.
[0054] Examples of the above-mentioned plasticizers include phthalate diesters such as dioctyl phthalate (DOP) and dibutyl phthalate (DBP), adipic acid diesters such as dioctyl adipate, and alkylene glycol diesters such as triethylene glycol-di-2-ethylhexanoate, tetraethylene glycol-di-2-ethylhexanoate, triethylene glycol-di-2-ethyl butyrate, tetraethylene glycol-di-2-ethyl butyrate, tetraethylene glycol-di-heptanoate, and triethylene glycol-di-heptanoate.
[0055] The above-mentioned dispersion enhancer is not particularly limited, but for example, fatty acids, aliphatic amines, alkanolamides, and phosphate esters are preferred. Silane coupling agents and the like may also be included. The above fatty acids are not particularly limited and include saturated fatty acids such as behenic acid, stearic acid, palmitic acid, myristic acid, lauric acid, capric acid, caprylic acid, and coconut fatty acid; and unsaturated fatty acids such as oleic acid, linoleic acid, linolenic acid, sorbic acid, beef tallow fatty acid, and hydrogenated castor fatty acid. Among these, lauric acid, stearic acid, and oleic acid are preferred. The above-mentioned aliphatic amines are not particularly limited and include, for example, laurylamine, myristylamine, cetylamine, stearylamine, oleylamine, alkyl(coconut)amine, alkyl(hydrogenated beef tallow)amine, alkyl(beef tallow)amine, alkyl(soybean)amine, etc. The above-mentioned alkanolamides are not particularly limited and include, for example, coconut fatty acid diethanolamide, beef tallow fatty acid diethanolamide, lauric acid diethanolamide, oleic acid diethanolamide, etc. The above-mentioned phosphate esters are not particularly limited, and examples include polyoxyethylene alkyl ether phosphate esters and polyoxyethylene alkyl allyl ether phosphate esters.
[0056] The method for producing the above-mentioned conductive paste is not particularly limited, and examples include mixing the above-mentioned polyvinyl acetal resin, the above-mentioned conductive powder, the above-mentioned organic solvent, and various additives added as needed using various mixers such as a ball mill, a blender mill, or a three-roll mill.
[0057] A multilayer ceramic capacitor can be obtained by applying the above-mentioned conductive paste onto a ceramic green sheet using a printing process, stacking multiple sheets, heating and pressing them together to create a laminate, then degreasing and firing to form a ceramic sintered body, and finally forming external electrodes on the end faces of the ceramic sintered body. The above-mentioned printing process can include screen printing, die coating, gravure offset, etc. Such a multilayer ceramic capacitor is also one of the present inventions. Furthermore, the polyvinyl acetal resin or the conductive paste according to one embodiment of the present invention can also be suitably used as a multilayer ceramic capacitor. Furthermore, a multilayer ceramic capacitor according to one aspect of the present invention can be manufactured by performing the steps of: applying a conductive paste according to one aspect of the present invention onto a ceramic green sheet; stacking multiple ceramic green sheets and heating and pressing them together to produce a laminate; degreasing and firing to produce a ceramic sintered body; and forming external electrodes on the end faces of the ceramic sintered body. [Effects of the Invention]
[0058] According to the present invention, it is possible to provide a polyvinyl acetal resin that can produce a conductive layer with good solvent solubility, high strength, and excellent adhesion, as well as a conductive paste and a multilayer ceramic capacitor using the polyvinyl acetal resin. Furthermore, according to the present invention, a conductive paste with high solvent solubility and appropriate viscosity can be obtained. [Modes for carrying out the invention]
[0059] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0060] (Example 1) (Preparation of polyvinyl acetal resin) 150 g of polyvinyl alcohol with a saponification degree of 99.0 mol% and an average degree of polymerization of 1700, and 13.5 g of Unisafe 10P-8 (polyoxyethylene polyoxypropylene cetyl ether, manufactured by NOF Corporation), diluted with pure water to a concentration of 20% by mass as a dispersant, were added to 1600 g of pure water and stirred at 90°C for 2 hours to dissolve. The solution was cooled to 65°C, and 160g of n-heptaldehyde was added. Then, it was cooled to 15°C, and 20g of 35% by mass hydrochloric acid, diluted in 180g of pure water, was added. The solution temperature was maintained at 15°C for 1 hour to allow the acetalization reaction to proceed, and the reaction product was precipitated. After 1 hour of the acetalization reaction, 13.5g of 20% by mass sodium dodecylbenzenesulfonate (SDBS) dissolved in pure water was added, and the acetalization reaction was continued for another hour. Next, the temperature was raised to 45°C at a rate of 2-3°C / 5 minutes, and the solution temperature was maintained at 45°C for 3 hours to complete the reaction. After neutralization, washing with water, and drying by conventional methods, a powder of polyvinyl acetal resin (long-chain alkyl modified) was obtained. The obtained polyvinyl acetal resin is dissolved in CDCl3 (deuterated chloroform), 1 H-NMR and 13 The content of each acetal unit, acetyl group, and hydroxyl group was measured using 1C-NMR (nuclear magnetic resonance spectroscopy). The total amount of acetal groups (sum of the content of each acetal unit) was also calculated from the measured values. The results are shown in Table 2. Note that the content of each acetal unit is as follows: 13 Quantitative analysis was performed using 1C-NMR. Note that the acetal unit is a constituent unit represented by the above formula (1) [R 1 = (CH2)5CH3]
[0061] (Example 2) 150 g of polyvinyl alcohol with a saponification degree of 99.4 mol% and an average degree of polymerization of 1700 was added to 1600 g of THF and dissolved by stirring at 65°C for 2 hours. The solution was cooled to 55°C, and 180g of 35% by weight hydrochloric acid and 150g of n-decylaldehyde were added. The mixture was reacted at 55°C for 6 hours, and then the solution was added to water to precipitate the resin, which was then recovered. After dissolving this resin again in 730g of THF, the resin was poured into an aluminum tray with the PET release film facing upwards, and dried in an 80°C oven for more than 5 hours to obtain a polyvinyl acetal resin film. The obtained polyvinyl acetal resin is dissolved in CDCl3 (deuterated chloroform), 1 H-NMR and13 The content of each acetal unit, acetyl group, and hydroxyl group was measured using 1C-NMR (nuclear magnetic resonance spectroscopy). The total amount of acetal groups (sum of the content of each acetal unit) was also calculated from the measured values. The results are shown in Table 2. Note that the content of each acetal unit is as follows: 13 Quantitative analysis was performed using 1C-NMR. Note that the acetal unit is the acetal unit [R] represented by the above formula (1). 1 = (CH2)8CH3]
[0062] (Example 3) (Preparation of polyvinyl acetal resin) 150 g of polyvinyl alcohol with a saponification degree of 98.4 mol% and an average degree of polymerization of 1700, and 13.5 g of Unisafe 10P-8 (polyoxyethylene polyoxypropylene cetyl ether, manufactured by NOF Corporation), diluted with pure water to a concentration of 20% by mass as a dispersant, were added to 1600 g of pure water and stirred at 90°C for 2 hours to dissolve. This solution was cooled to 65°C, and 70 g of n-butyraldehyde and 79 g of n-heptaldehyde were added. Then, it was cooled to 15°C, and 20 g of 35% by mass hydrochloric acid was added, diluted with 180 g of pure water. The solution temperature was maintained at 15°C for 1 hour to carry out the acetalization reaction and precipitate the reaction product. After 1 hour of the acetalization reaction, 13.5 g of 20% by mass sodium dodecylbenzenesulfonate (SDBS) dissolved in pure water was added, and the acetalization reaction was carried out for another hour. Next, the temperature was raised to 45°C at a rate of 2-3°C / 5 minutes, and the solution temperature was maintained at 45°C for 3 hours to complete the reaction. After neutralization, washing with water, and drying by conventional methods, a powder of polyvinyl acetal resin (long-chain alkyl modified) was obtained. The obtained polyvinyl acetal resin is dissolved in CDCl3 (deuterated chloroform), 1 H-NMR and 13 The content of each acetal unit, acetyl group, and hydroxyl group was measured using 1C-NMR (nuclear magnetic resonance spectroscopy). The total amount of acetal groups (sum of the content of each acetal unit) was also calculated from the measured values. The results are shown in Table 2. Note that the content of each acetal unit is as follows: 13 Quantitative analysis was performed using 1C-NMR. Note that the acetal unit is a constituent unit represented by the above formula (1) [R 1 =(CH2)5CH3] and the constituent unit represented by the above formula (2) [R 2 =(CH2)2CH3]
[0063] (Example 4) (Preparation of polyvinyl acetal resin) 150 g of polyvinyl alcohol with a saponification degree of 99.0 mol% and an average degree of polymerization of 1700, and 13.5 g of Unisafe 10P-8 (polyoxyethylene polyoxypropylene cetyl ether, manufactured by NOF Corporation), diluted with pure water to a concentration of 20% by mass as a dispersant, were added to 1600 g of pure water and stirred at 90°C for 2 hours to dissolve. This solution was cooled to 65°C, and 80 g of n-butyraldehyde and 87 g of n-heptaldehyde were added. Then, it was cooled to 15°C, and 20 g of 35% by mass hydrochloric acid was added, diluted with 180 g of pure water. The solution temperature was maintained at 15°C for 1 hour to carry out the acetalization reaction and precipitate the reaction product. After 1 hour of the acetalization reaction, 13.5 g of 20% by mass sodium dodecylbenzenesulfonate (SDBS) dissolved in pure water was added, and the acetalization reaction was carried out for another hour. Next, the temperature was raised to 45°C at a rate of 2-3°C / 5 minutes, and the solution temperature was maintained at 45°C for 3 hours to complete the reaction. After neutralization, washing with water, and drying by conventional methods, a powder of polyvinyl acetal resin (long-chain alkyl modified) was obtained. The obtained polyvinyl acetal resin is dissolved in CDCl3 (deuterated chloroform), 1 H-NMR and 13 The content of each acetal unit, acetyl group, and hydroxyl group was measured using 1C-NMR (nuclear magnetic resonance spectroscopy). The total amount of acetal groups (sum of the content of each acetal unit) was also calculated from the measured values. The results are shown in Table 2. Note that the content of each acetal unit is as follows: 13 Quantitative analysis was performed using 1C-NMR. Note that the acetal unit is a constituent unit represented by the above formula (1) [R 1 =(CH2)5CH3] and the acetal unit [R] represented by the above formula (2). 2 =(CH2)2CH3]
[0064] (Example 5) 150 g of polyvinyl alcohol with a saponification degree of 99.4 mol% and an average degree of polymerization of 800 was added to 1600 g of THF and dissolved by stirring at 65°C for 2 hours. The solution was cooled to 55°C, and 180g of 35% by weight hydrochloric acid and 150g of n-decylaldehyde were added. The mixture was reacted at 55°C for 6 hours, and then the solution was added to water to precipitate the resin, which was then recovered. After dissolving this resin again in 730g of THF, the resin was poured into an aluminum tray with the PET release film facing upwards, and dried in an 80°C oven for more than 5 hours to obtain a polyvinyl acetal resin film. The obtained polyvinyl acetal resin is dissolved in CDCl3 (deuterated chloroform), 1 H-NMR and 13 The content of each acetal unit, acetyl group, and hydroxyl group was measured using 1C-NMR (nuclear magnetic resonance spectroscopy). The total amount of acetal groups (sum of the content of each acetal unit) was also calculated from the measured values. The results are shown in Table 2. Note that the content of each acetal unit is as follows: 13 Quantitative analysis was performed using 1C-NMR. Note that the acetal unit is the acetal unit [R] represented by the above formula (1). 1 = (CH2)8CH3]
[0065] (Example 6) (Preparation of polyvinyl acetal resin) 150 g of polyvinyl alcohol with a saponification degree of 92.0 mol% and an average degree of polymerization of 1700, and 13.5 g of Unisafe 10P-8 (polyoxyethylene polyoxypropylene cetyl ether, manufactured by NOF Corporation), diluted with pure water to a concentration of 20% by mass as a dispersant, were added to 1600 g of pure water and stirred at 90°C for 2 hours to dissolve. This solution was cooled to 65°C, and 106 g of n-butyraldehyde and 45 g of n-heptaldehyde were added. Then, it was cooled to 15°C, and 20 g of 35% by mass hydrochloric acid, diluted in 180 g of pure water, was added. The solution temperature was maintained at 15°C for 1 hour to allow the acetalization reaction to proceed, and the reaction product was precipitated. After 1 hour of the acetalization reaction, 13.5 g of 20% by mass sodium dodecylbenzenesulfonate (SDBS) dissolved in pure water was added, and the acetalization reaction was continued for another hour. Next, the temperature was raised to 45°C at a rate of 2-3°C / 5 minutes, and the solution temperature was maintained at 45°C for 3 hours to complete the reaction. After neutralization, washing with water, and drying by conventional methods, a polyvinyl acetal resin (long-chain alkyl modified) powder was obtained. The obtained polyvinyl acetal resin is dissolved in CDCl3 (deuterated chloroform), 1 H-NMR and 13 The content of each acetal unit, acetyl group, and hydroxyl group was measured using 1C-NMR (nuclear magnetic resonance spectroscopy). The total amount of acetal groups (sum of the content of each acetal unit) was also calculated from the measured values. The results are shown in Table 2. Note that the content of each acetal unit is as follows: 13 Quantitative analysis was performed using 1C-NMR. Note that the acetal unit is a constituent unit represented by the above formula (1) [R 1 =(CH2)5CH3] and the constituent unit represented by the above formula (2) [R 2 =(CH2)2CH3]
[0066] (Comparative Example 1) (Preparation of polyvinyl acetal resin) 150 g of polyvinyl alcohol with a saponification degree of 98.5 mol% and an average degree of polymerization of 1700 was added to 1600 g of pure water and dissolved by stirring at 90°C for 2 hours. The solution was cooled to 40°C, and 120 g of 35% by mass hydrochloric acid was added. Then, the solution was cooled to 10°C, and 130 g of acetaldehyde was added to carry out the acetalization reaction, precipitating the reaction product. Next, the solution temperature was maintained at 30°C for 6 hours to complete the reaction, and after neutralization, washing with water, and drying by conventional methods, a polyvinyl acetal resin powder was obtained. The obtained polyvinyl acetal resin is dissolved in CDCl3 (deuterated chloroform), 1 The content of each acetal unit, acetyl group, and hydroxyl group was measured using 1H-NMR (nuclear magnetic resonance spectroscopy). The total acetal group content (sum of the content of each acetal unit) was also calculated from the measured values. The results are shown in Table 2. Note that the acetal unit was actually the acetacetal unit.
[0067] (Comparative Example 2) (Preparation of polyvinyl acetal resin) 150 g of polyvinyl alcohol with a saponification degree of 98.5 mol% and an average degree of polymerization of 1700 was added to 1600 g of pure water and dissolved by stirring at 90°C for 2 hours. The solution was cooled to 40°C, and 120 g of 35% by mass hydrochloric acid was added. Then, the solution was cooled to 10°C, and 160 g of n-butyraldehyde was added to carry out the acetalization reaction, precipitating the reaction product. Next, the solution temperature was maintained at 30°C for 6 hours to complete the reaction, and after neutralization, washing with water, and drying by conventional methods, a polyvinyl acetal resin powder was obtained. The obtained polyvinyl acetal resin is dissolved in CDCl3 (deuterated chloroform), 1 The content of each acetal unit, acetyl group, and hydroxyl group was measured using 1H-NMR (nuclear magnetic resonance spectroscopy). The total acetal group content (sum of the content of each acetal unit) was also calculated from the measured values. The results are shown in Table 2. The acetal unit was equivalent to the butyral unit.
[0068] (Comparative Example 3) (Preparation of polyvinyl acetal resin) 300 g of ethylene oxide-modified polyvinyl alcohol resin (ethylene oxide modification amount 3 mol%) with a saponification degree of 99.3 mol% and an average degree of polymerization of 700 was added to 2800 g of pure water and dissolved by stirring at 90°C for 2 hours. The solution was cooled to 40°C, and 300 g of 35% by mass hydrochloric acid was added. Then, the solution was cooled to 30°C, and 200 g of n-butyraldehyde was added to carry out the acetalization reaction, precipitating the reaction product. Next, the solution temperature was maintained at 45°C for 4 hours to complete the reaction, and after neutralization, washing with water, and drying by conventional methods, a polyvinyl acetal resin powder was obtained. The obtained polyvinyl acetal resin is dissolved in DMSO-D6 (didimethyl sulfoxide), 1 Using 1H-NMR (nuclear magnetic resonance spectroscopy), the content of each acetal unit, the amount of acetyl groups, the amount of hydroxyl groups, and the amount of alkylene oxide modification were measured. The total amount of acetal groups (sum of the content of each acetal unit) was also calculated from the measured values. The results are shown in Table 2. The acetal unit was equivalent to the butyral unit.
[0069] <Rating> The obtained polyvinyl acetal resin was evaluated as follows.
[0070] (1) Relaxation time ratio The relaxation time ratio was measured under the conditions shown in Table 1. Specifically, the following procedure was used. Side chain ends and main chain 1 T of the H nucleus 1ρ To determine the relaxation time ratio, 13 C spectral observation 1 T of the H nucleus 1ρ A pulse sequence was used to observe the relaxation time. In this pulse sequence, the magnetization was attenuated by a spinlock measurement of a normal 1H nucleus, and the residual after the delay time was 1 The magnetization of the H nucleus is determined by cross-polarization (CP). 13 The sample was moved to C and then the FID was observed. Polyvinyl acetal resin was packed into a 4 mm rotor for solid-state NMR, and the measurement was performed using a solid-state NMR analyzer (JEOL Ltd., ECZ-400R). The sample temperature at that time was room temperature, and the observed nuclei were 13 C, MAS speed 10kHz, 1Measurements were taken using the aforementioned pulse sequence with a 90-degree pulse width of 2.93 μs for the H nucleus and a CP contact time of 1 ms. The CP conditions were optimized for the standard sample. The spinlock conditions were as follows: 1 The pulse attenuation of the H nucleus was set to 3 dB, and spin-locked at 50% of that output. In the relaxation time measurement, the first time point τmin was set to 100 μs, and the last time point τmax was set to 4 ms, with 14 time points in logarithmic increments between them. 13 The 1C-NMR spectrum was measured. solid 13 By plotting the signal intensity from acetal carbons around 88 ppm to 105 ppm in the 1C-NMR spectrum against the spinlock time, the acetal 1 H's T 1ρ Relaxation curves were obtained. Similarly, from the intensity decay of methine carbon around 57 ppm to 90 ppm, 1 H's T 1ρ The relaxation curve is derived from the intensity decay of the side-chain terminal methyl carbon around 10 ppm to 20 ppm. 1 H's T 1ρ The transition curves were calculated. The integral values were calculated after baseline correction of the signal region using a linear function. These transition curves were fitted using the least squares method with an exponential damping function consisting of one or two terms, and the coefficients of each term and each 1 T of the H nucleus 1ρ The relaxation time was calculated. When a two-term decay function was used, the weighted average relaxation time for the coefficient of each term was calculated for the T of the functional group. 1ρ This was designated as a relaxation period. These three types of T 1ρ During the relaxation time, methine 1 H and acetal 1 T derived from H 1ρ The average relaxation time is the T of the main chain of the polyvinyl acetal resin. 1ρ T is the relaxation time. 1ρ [MC] was used. 1 H's T 1ρ The relaxation time was defined as the T1ρ relaxation time at the side chain terminus, T1ρ[T], and the ratio, T1ρ[T] / T1ρ[MC], was calculated.
[0071] [Table 1]
[0072] (2) Measurement of glass transition temperature The glass transition temperature (Tg) of the obtained polyvinyl acetal resin was measured using a differential scanning calorimeter (DSC).
[0073] (3) Adhesion strength [Tack test] 10.0 parts by weight of the obtained polyvinyl acetal resin, 1.5 parts by weight of a plasticizer (Sekisui Chemical Co., Ltd., G260), and 50 parts by weight of an ethanol / toluene mixed solvent (weight ratio 1:1) were added and stirred to dissolve, thereby obtaining a polyvinyl acetal resin composition. The obtained polyvinyl acetal resin composition was coated onto a PET film that had been released using a coater to a thickness of 20 μm after drying, and then heated and dried to produce a polyvinyl acetal resin sheet. The obtained polyvinyl acetal resin sheet was cut into 7cm x 7cm pieces to serve as test specimens. Using a tacking test machine (Lesca, TAC1000) equipped with a φ5mm probe, the plate and probe were set to 65°C, the test specimen was placed on the stage and heated for 20 minutes, and then the tack force was measured. At this time, the pressing speed was 1mm / s, the pressing load was 400gf, the pressing holding time was 30 seconds, and the lifting speed was 1mm / s. The peak load value at the time of lifting was measured as the tack force. A total of five measurements were taken at different locations on the test specimen, and the average tack force value was determined according to the evaluation criteria below.
[0074] AA:300gf or more A: 200gf or more, less than 300gf B: 100gf or more, less than 200gf C: Less than 100gf
[0075] (4) Sheet strength [strain at fracture point] The obtained polyvinyl acetal resin sheet was cut into 5cm x 1cm pieces to serve as test specimens. Using a tensile testing machine (Shimadzu Corporation, AUTOGRAPH AGS-J), the chuck distance was set to 1.5cm, and the specimens were pulled at a tensile speed of 100mm / min. The fracture strain (%) was measured at a measurement temperature of 20°C. The results were evaluated according to the evaluation criteria below.
[0076] (Fracture point strain) AA: 350% or more A: 290% or more, less than 350% B: 200% or more, less than 290% C: Less than 200%
[0077] (5) Solvent solubility A 30g solution was prepared in a sealed glass container by mixing polyvinyl acetal resin and dihydroterpinyl acetate to a concentration of 10% by mass. The solution was stirred at room temperature for 1 hour using a stirrer, then heated to 90°C using a hot stirrer and stirring was continued. The solution state was visually inspected and evaluated according to the following criteria. Dissolution was confirmed by visually observing the solution in a transparent glass container under a white background and confirming that no solid matter remained (complete dissolution).
[0078] A: Completely dissolves in less than 3 hours B: Completely dissolves in 3 hours to less than 7 hours. C: Even after more than 7 hours, some residue remains.
[0079] [Table 2] [Industrial applicability]
[0080] According to the present invention, it is possible to provide a polyvinyl acetal resin that can produce a conductive layer with good solvent solubility, high strength, and excellent adhesion, as well as a conductive paste and a multilayer ceramic capacitor using the polyvinyl acetal resin.
Claims
1. A polyvinyl acetal resin in which the ratio of the relaxation time T1ρ[T] obtained from the side-chain terminal carbon to the average relaxation time T1ρ[MC] of the acetal carbon and methine carbon, calculated by solid-state NMR, is 1.3 or greater (T1ρ[T] / T1ρ[MC]).
2. It has a constituent unit represented by the following formula (1), and R in the following formula (1) 1 The polyvinyl acetal resin according to claim 1, wherein the hydrocarbon group is linear and has 4 to 20 carbon atoms, and the average degree of polymerization is less than 2300. 【Chemistry 1】
3. The polyvinyl acetal resin according to claim 1 or 2, wherein the glass transition temperature is 60°C or lower.
4. The polyvinyl acetal resin according to claim 1 or 2, wherein the amount of hydroxyl groups is 10 mol% or more and 25 mol% or less.
5. The polyvinyl acetal resin according to claim 1 or 2, wherein the content of the constituent unit represented by formula (1) is 5 mol% or more and 45 mol% or less.
6. A conductive paste comprising the polyvinyl acetal resin described in claim 1 or 2, an organic solvent, a conductive powder, and a dispersion improver.
7. A multilayer ceramic capacitor comprising the conductive paste described in claim 6.
Citation Information
Patent Citations
Modified polyvinyl acetal resin, coating paste, conductive paste, and ceramic paste
JP2008285590A
Conductive paste
JP2017228780A